To the question of the role of person’s acmeological culture in the professional activity - Stepanyan, Lusibe (Przegląd Wschodnioeuropejski, 2018)
The problem of person’s acmeological culture in the field of personal and professional activity was investigated. The dynamic model of acmeological culture of person, which consists of such functional elements as self-estimate, motivation and active life position, was described. The role of the acmeological culture was shown as integrative factor, which stimulates the process of achievement of “acme” in all spheres of human activity through understanding, realization and actualization of their needs, values and interests.